1999
DOI: 10.1021/js980225w
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Kinetics of Rotamer Interconversion in Immunosuppressant Prodigiosin Derivatives in Solution

Abstract: The equilibrium and relative rate of rotamer interconversion around the bond joining the 2,2'-bipyrrolyl and pyrromethene moieties in a synthetic analogue of immunosuppressant prodigiosin are investigated as a function of pHapp in a water/acetonitrile mixture (1/1 by volume). Two chromatographically separable isomeric forms are obtained in acid solutions (pHapp < 4), whereas rapid interconversion occurs above neutrality. Furthermore, pH modulates the conformational preference of the molecule according to nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 7 publications
(6 reference statements)
4
39
0
2
Order By: Relevance
“…The BMAP-28-treated U937 cell line revealed that some AMPs are endowed with cytotoxic mechanisms also involving triggering of cancer cell suicide by apoptosis (Rizzo et al, 1998). The results of the present study demonstrate.…”
Section: Discussionsupporting
confidence: 68%
“…The BMAP-28-treated U937 cell line revealed that some AMPs are endowed with cytotoxic mechanisms also involving triggering of cancer cell suicide by apoptosis (Rizzo et al, 1998). The results of the present study demonstrate.…”
Section: Discussionsupporting
confidence: 68%
“…While one solution would be to protect the amine as the hydrochloride salt, it was known that the protonated forms of prodiginines such as undecylprodigiosin and PNU-156804 ( 208 ) favored the trans- rotomeric configuration (Figure 27). 106 …”
Section: Total Synthesesmentioning
confidence: 99%
“…The 1 H NMR spectrum of 8 in CDCl 3 ( Figure S3, Supporting Information) showed a single set of resonances, indicating the symmetrical nature of the Zn complex, with the NH proton of the A-pyrrole ring resonating at δ 9.27 ppm. This chemical shift is upfield by ∼3 ppm of the corresponding NH proton in protonated prodigiosin, 21 suggesting that the A-ring NH proton is shielded by the aromatic nucleus of the other Zn-bound prodigiosin molecule.…”
mentioning
confidence: 99%